V(D)J Rearrangement Is Dispensable for Producing CDR-H3 Sequence Diversity in a Gene Converting Species - Leighton, Philip A.; Morales, Jacqueline; Harriman, William D.; Ching, Kathryn H. (Frontiers in Immunology, 2018)
An important characteristic of chickens is that the antibody repertoire is based on a single framework, with diversity found mainly in the CDRs of the light and heavy chain variable regions. Despite this apparent limitation in the antibody repertoire, high affinity antibodies can be raised to a wide variety of targets, including those that are highly conserved. Transgenic chickens have previously been generated that express a humanized antibody repertoire, with a single framework that incorporates diversity by the process of gene conversion, as in wild type chickens. Here we compare the sequences and antibodies that are generated purely by gene conversion/somatic hypermutation of a pre-rearranged heavy chain, with the diversity obtained by V(D)J rearrangement followed by gene conversion and somatic hypermutation. In a gene converting species, CDR-H3 lengths are more variable with V(D)J rearrangement, but similar levels of amino acid diversity are obtainable with gene conversion/somatic hypermutation alone.